Towards social acceptability of genome-edited plants in industrialised countries? Emerging evidence from Europe, United States, Canada, Australia, New Zealand, and Japan - Spök, Armin; Sprink, Thorben; Allan, Andrew C.; Yamaguchi, Tomiko; Dayé, Christian (Frontiers in Genome Editing, 2022)
The agricultural biotechnology world has been divided into two blocks; countries adopting GM crops for commercial cultivation (adopters) and others without any or without relevant cultivation of such crops (non-adopters). Meanwhile, an increasing number of adopter countries have exempted certain genome-edited (GE) crops from legal GMO pre-market approval and labelling requirements. Among them are major exporters of agricultural commodities such as USA, Canada, and Australia. Due to the relaxed legislation more GE plants are expected to enter the market soon. Many countries in the non-adopter group, however, depend on import of large volumes of agricultural commodities from adopter countries. Unlike first generation GM, certain GE crops cannot be identified as unambiguously originating from genome editing using available techniques. Consequently, pressure is mounting on non-adopter jurisdictions to reconsider their policies and legislations. Against this backdrop, the paper explores recent developments relevant for social acceptability in selected non-adopters, Japan, New Zealand, the EU, Norway, and Switzerland in contrast to USA, Canada, and Australia. While Japan is already opening-up and Norway and Switzerland are discussing revisions of their policies, the EU and New Zealand are struggling with challenges resulting from high court decisions. In an attempt to take a closer look into the inner dynamics of these developments, the concept of social acceptability proposed by Wüstenhagen et al. (2007) is employed. This aids the understanding of developments in the jurisdictions considered and identifies specific or cross-cutting challenges.